THE RELATIONSHIP OF INNOVATIVE ATTITUDE WITH CRITICAL THINKING ABILITY OF CLASS XI IPS SMAN 2 PANDEGLANG - Yudi Ahyudin; Sholeh Hidayat; Suherman (Econosains Jurnal Online Ekonomi dan Pendidikan, 2021)
This study aims to determine the relationship between innovative attitudes and critical thinking skills of class XI IPS students at SMAN 2 Pandeglang. The research was carried out in the form of field research while the method used was a correlational survey. The population in this study were all students of class XI social studies cluster even semester 2020/2021 academic year, as many as 6 classes with a total of 207 social studies cluster students. In this research, random sampling technique is used, namely a sample in such a way that each research unit from the population has an equal opportunity to be selected as a sample. The results showed that there is a relationship between positive innovative attitudes and critical thinking skills of class XI IPS students at SMAN 2 Pandeglang. On the significance level α = 0,05 with n = 67 got rtable 0,204. As a result rcounting 0,860> rtable 0,204 Students who have a good innovative attitude will certainly acquire high critical thinking skills. Students who have a bad innovative attitude will get low thinking skills. Thus, there is a positive relationship between innovative attitudes and critical thinking skills in class XI IPS SMAN 2 Pandeglang.